2018
DOI: 10.3390/ma11081408
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Production of Levulinic Acid and Porous Carbon Material from Cellulose

Abstract: A sequential production of levulinic acid (LA) and porous carbon material (CM) from cellulose was conducted by a two-step process. The cellulose was first acid hydrolyzed, and the preferred reaction conditions required a severity factor of 4.0–4.5, in which the yields of LA, formic acid, and solid residue were 38 ± 3 wt%, 17 ± 3 wt%, and 15 ± 3 wt%, respectively. The solid residue was further used for CM preparation through pyrolysis, with or without ZnCl2 activation. The ZnCl2 activation promoted the formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The SSAs obtained for BCs and PHCs from cellulose correspond well with literature, since similar SSAs were obtained by Kang et al [81] on pyrolyzed cellulosic hydrochar. The type IV isotherms observed for PHCs from cellulose (Figure 7B) indicate the presence of macropores.…”
Section: Discussionsupporting
confidence: 89%
“…The SSAs obtained for BCs and PHCs from cellulose correspond well with literature, since similar SSAs were obtained by Kang et al [81] on pyrolyzed cellulosic hydrochar. The type IV isotherms observed for PHCs from cellulose (Figure 7B) indicate the presence of macropores.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, sub-micropore and mesopore architectures within a porous structure provide interconnected channels throughout the fast charge/discharge route, leading to a high rate capability and enhanced charge storage capacity. Macropores also deliver ion buffering reservoirs, which shorten ion diffusion pathways into internal porosity assuring decrease in the electric resistance. According to the International Union of Pure and Applied Chemistry, a micropore is categorized as a pore with a diameter of less than 2 nm, while a pore with size ranging between 2 and 50 mm is considered to be a mesopore, and the pore size of a macropore is larger than 50 nm …”
Section: Introductionmentioning
confidence: 99%
“…Preliminary investigations are being made and forwarded to the valuation of HUs approaching the structure and its formation mechanism [14,46]. Recently, it was demonstrated that HUs generally contained a carbon content of 60-80 wt% [55], which indicated that more than 30% of the initial carbon in cellulose was wasted as solid carbonaceous residue. As a material with high carbon content, Kang et al [55], showed that about 74.4% of the initial carbon of cellulose was transferred into value-added products, (47% carbon in LA), and also 16.1% in carbon adsorbents, especially for wastewater treatment.…”
Section: The Challenge Of the Current Circular Economy In Valuing Husmentioning
confidence: 99%
“…Recently, it was demonstrated that HUs generally contained a carbon content of 60-80 wt% [55], which indicated that more than 30% of the initial carbon in cellulose was wasted as solid carbonaceous residue. As a material with high carbon content, Kang et al [55], showed that about 74.4% of the initial carbon of cellulose was transferred into value-added products, (47% carbon in LA), and also 16.1% in carbon adsorbents, especially for wastewater treatment. HUs represent a matrix rich in carbon and furanic structures with hydroxyl and carbonyl functional groups.…”
Section: The Challenge Of the Current Circular Economy In Valuing Husmentioning
confidence: 99%